Study of the Greitzer Model for Centrifugal Compressors: Variable Lc Parameter and Two Types of Surge - Filip Grapow; Grzegorz Liśkiewicz (Energies, 2020)
In this paper, the Greitzer surge model was systematically analysed with the model compressor duct length Lc as the tuning parameter. The surge phenomenon is known to induce a serious risk to centrifugal compressor operation. The two-dimensional Greitzer model is a well-established way of modelling this dangerous instability, but the determination and changes of the model parameters are still being discussed. In this paper an automated procedure determines the Lc value providing the best fit with the experimental data has been presented. The algorithm was tested on five valve positions and revealed that the best fit was obtained for different Lc values following a linear trend against the mass flow rate. The study has also shown that the Greitzer model has two solutions for a given pressure oscillation amplitude: one similar to the deep surge (low Lc) and one similar to the mild surge (low Lc). This suggests that this model can be used to simulate both types of the phenomenon known from the experimental analyses. The study proposes the dimensionless average pressure as the parameter allowing to distinguish which surge cycle was observed at a given instance. Past papers were analysed to observe the surge type that appeared in different experiments. It was found that most researchers obtained low Lc surge. The results show that both deep and mild surge could be simulated with the Greitzer model. It also revealed that the Lc should not be treated as a constant value for a given machine and that it changes with the mass flow rate.